Factor Influencing Purchase Intention for Co-Branded Anime Fashion Products - Raisy, Raisy; Fahlevi, Renza; Sinambela, Fitriana Aidnilla (Jambura Science of Management, 2024)
Purpose: The analysis conducted in this study was done by computing and comprehending output derived from quantitative and qualitative data collected from consumers of Co-Branded Anime Products. This study strives to contribute to the scarce research regarding the effects of factors like product, price, place, promotion, and attitude toward the purchase intention for Co-Branded anime fashion products.Design/Methodology/Approach: This study was conducted with the technological assistance of IBM SPSS Statistics 26 to compute quantitative data from Co-Branded Anime Fashion Products consumers which were collected through Google Forms. Samples were determined using the method practiced by Hair et al. (2014). Qualitative data for this study was collected through fill-in questionnaires which were distributed to three consumers of Co-Branded Anime Fashion Products and analysed concurrently.Findings: What affects the purchase intention for Co-branded Anime Fashion Products is rarely, if not, ever studied despite its rising popularity in the modern age. This study concludes that determinants such as product, place, and attitude significantly influence the purchase intention for Co-branded Anime Fashion Products. In contrast, price and promotion do not, the reason being that the intention to purchase products of this nature is mostly driven by consumers' interest and dedication to the collaborator (anime) featured on the products themselves.